Occupational mobility in nineteenth century rural England: the interpretation of entheseal changes - Henderson, Charlotte Yvette (2013)
Identified skeletal collections have been widely used to test methods for recording entheseal changes. These studies have all used the occupation provided with the death certificate or equivalent as the occupation during life. However, the variety of tasks undertaken within occupations, the range of occupational tasks and how these changed over the life course is rarely discussed. The aim of this paper is to highlight the value of using historical data to improve the interpretation of skeletal data. Materials and Methods: Identified adult skeletons (n=18), from the churchyard of St. Michael and St. Lawrence, Fewston, North Yorkshire, England were recorded for entheseal changes (EC) and degenerative joint changes (DJC). The individuals were born and died between 1791 – 1921 (only one individual was buried after the churchyard's closure in 1896). All individuals have at least one census record which includes their occupation. Published sections of a diary coinciding with the cemetery’s use and written by the son of two of the identified individuals were used to record the frequency and range of activities. Results: 54.5% of males and 29% of females changed their occupations and those who changed occupation were found to be older than those who did not. The latter were found to have a lower frequency of DJC and EC, but this is likely due to the difference in age profile between the two groups. However, the detailed pattern of EC did not match that of DJC for the three occupation categories used. The diary demonstrated that a stonemason undertook a wide variety of occupational tasks as well as enjoying hobbies. Discussion: The results demonstrate that occupations in nineteenth century rural England were not stable and demonstrated a wide variety of everyday and infrequent activities. This demonstrates that using occupation listed at death does not provide sufficiently detailed information for testing methods of recording EC or for interpreting the relationship between occupation and health.